Earthquakes control the impulsive nature of crustal helium degassing to the atmosphere - Antonio Caracausi; Dario Buttitta; Matteo Picozzi; Michele Paternoster; Tony Alfredo Stabile (Communications Earth & Environment, 2022)
Crustal degassing of 4He from fault zones occurs throughout the seismic cycle which suggests variations in this flux could be a valuable seismic monitoring tool, according to an analysis of He flux calculations and seismic data from the Irpinia Fault Zone, Italy.